1993
DOI: 10.1215/03616878-18-1-27
|View full text |Cite
|
Sign up to set email alerts
|

The Limits of Marginal Economic Incentives in the Medicaid Program: Concerns and Cautions

Abstract: In January 1985, New York State implemented legislation that allowed for a 30 percent increase in Medicaid fees for physicians providing primary care services. This was intended to increase their levels of participation. Yet the outcome was not as expected. In upstate New York, the number of physicians participating in Medicaid each month actually declined; in New York City, the monthly rate of increase in participating physicians, which was part of the overall sharp rise in all licensed physicians, underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…Although the size of Medicaid payments does not appear to enhance such connections for insured residents, larger Medicaid payments do promote insured adults' use of physician services. This finding is consistent with the mixed, but generally weak, effects of Medicaid fees on physician participation and volume of physician visits found in other studies (Mitchell 1991;Fanning and de Alteriis 1993;Adams 1994;Coburn, Long, and Marquis 1999). Thus, the answer to our third research question is that the effect of support for the community's safety net varies by health insurance status, with greater support translating into better potential access for the uninsured and better realized access for insured residents.…”
Section: Discussionsupporting
confidence: 91%
“…Although the size of Medicaid payments does not appear to enhance such connections for insured residents, larger Medicaid payments do promote insured adults' use of physician services. This finding is consistent with the mixed, but generally weak, effects of Medicaid fees on physician participation and volume of physician visits found in other studies (Mitchell 1991;Fanning and de Alteriis 1993;Adams 1994;Coburn, Long, and Marquis 1999). Thus, the answer to our third research question is that the effect of support for the community's safety net varies by health insurance status, with greater support translating into better potential access for the uninsured and better realized access for insured residents.…”
Section: Discussionsupporting
confidence: 91%
“…Evidence concerning the importance of Medicaid reimbursement rates as a driver of access to primary care services for the poor is also substantially equivocal. Several studies suggest that fee increases have small to moderate effects on primary care physicians' Medicaid participation levels (Berman et al 2002;Coburn, Long, and Marquis 1999;Fanning and de Alteriis 1993;Gray, Vandergrift, and McAllister 2015;Perloff, Kletke, and Fossett 1995;Perloff et al 1997;Wilk 2013;Zuckerman et al 2004), and emerging studies on the effects of the fee bump itself are similarly mixed (Crawford and McGinnis 2015;Decker 2016;MACPAC 2015;Mulcahy et al 2016;Polsky et al 2015). Other factors such as delays in payment, administrative burden, and perceptions of patient difficulty might be equally or more consequential Nichols 2005, Cunningham andO'Malley 2009;Davidson 1982;GAO 2011;Hadley 1979;Long 2013;Spaulding 2015;Wilk 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Most recent studies of fee increases have found that their average effects on PCP participation are only small to moderate (Berman et al 2002;Coburn, Long, and Marquis 1999;Fanning and de Alteriis 1993;Perloff, Kletke, and Fossett 1995;Perloff et al 1997;Wilk 2013;Zuckerman et al 2004), though effects will be more significant for some physicians than for others (Wilk 2013). Thus, quite substantial fee increases may be required to achieve meaningful improvements in PCP participation.…”
Section: Introductionmentioning
confidence: 99%